A Study On Job Satisfaction Of Migrant Labourers In Kerala With Reference To Mavelikara Taluk - et. al., Karun, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The most valuable commodity in the economy sector is human resource, whether organised or unorganised. Work satisfaction is the feelings, behaviours or desire about work and culture of an individual. A happy worker is said to have a positive attitude toward their work, while a dissatisfied worker is said to have a negative attitude toward their work. The researcher looked at migrant workers' satisfaction in different aspects. Standard working hours, regularity of payments, overtime wages offered, safety measures, working conditions, employer-employee relationship, bonus given, relationship with local residents, and job satisfaction were all highly rated by the majority of respondents. The present study is limited at Mavelikkara Taluk of Alappuzha district of Kerala, India.